The Impact of IKN on Socio-Economic Development in Penajem Paser Utara (PPU) and Kutai Kartanegara - B, Jauchar; Budiman, Budiman; Idris, Adam; Nasir, Badruddin; Khaerunnisa, Ayu (Universitas Muhammadiyah Yogyakarta, 2022)
The construction of a New Capital City (IKN) will have major implications for the equitable distribution of national welfare. The development of the National Capital Region (IKN) is a national strategic project that is considered to be able to increase economic growth and equitable distribution of national welfare. There are data that explain empirically the explanatory material that has been discussed. It can be emphasized that in the short term, the development of the IKN can encourage economic activity through infrastructure investment in the IKN and surrounding areas. Then encourage trade between regions, and open up job creation opportunities. This paper also recommends that development in the context of welfare is not only a matter of increasing economic impact after the development of IKN in PPU and Kukar. However, in the context of the perspective of local community involvement in the stages of IKN development, it must be included, especially the contribution to recommendations for strengthening the socio-cultural aspect. The analysis used in this paper is descriptive qualitative research. In collecting data to support this research will track through data from the Central Statistics Agency (BPS) and National Development Planning Agency (BAPPENAS) for each area affected by IKN.